Superglue in First Aid Boxes (International Journal of First Aid Education)
Advocates for 2-octyl cyanoacrylate (Super Glue) in household first aid kits, looking over the history of its use, risks and merits, and arguing that it will reduce unnecessary and avoidable admittances to emergency departments.